Jati Denok: Big Book Media as an Effort to Improve Poetry Reading Skills of Second Grade Students in Elementary School - Afifah, Nur Ummi; Purwati, Panca Dewi; Sismulyasih SB, Nugraheti (Universitas Pendidikan Ganesha, 2024)
The low level of reading skills is one of the fundamental problems that occurs in elementary schools. Low initial reading skills indicate this. This research aims to develop learning media in the form of the Big Book